Single Point Insulin Sensitivity Estimator in Pediatric Non-Alcoholic Fatty Liver Disease - Furthner, Dieter; Anderwald, Christian-Heinz; Bergsten, Peter; Forslund, Anders; Kullberg, Joel; Ahlström, Håkan; Manell, Hannes; Ciba, Iris; Mangge, Harald; Maruszczak, Katharina; Koren, Pia; Schütz, Sebastian; et al. (Frontiers in Endocrinology, 2022)
BACKGROUND Attenuated insulin-sensitivity (IS) is a central feature of pediatric non-alcoholic fatty liver disease (NAFLD). We recently developed a new index, single point insulin sensitivity estimator (SPISE), based on triglycerides, high-density-lipoprotein and body-mass-index (BMI), and validated by euglycemic-hyperinsulinemic clamp-test (EHCT) in adolescents. This study aims to assess the performance of SPISE as an estimation of hepatic insulin (in-) sensitivity. Our results introduce SPISE as a novel and inexpensive index of hepatic insulin resistance, superior to established indices in children and adolescents with obesity. MATERIALS AND METHODS Ninety-nine pubertal subjects with obesity (13.5±2.0 years, 59.6% males, overall mean BMI-SDS + 2.8±0.6) were stratified by MRI (magnetic resonance imaging) into a NAFLD (>5% liver-fat-content; male n=41, female n=16) and non-NAFLD (≤5%; male n=18, female n=24) group. Obesity was defined according to WHO criteria (> 2 BMI-SDS). EHCT were used to determine IS in a subgroup (n=17). Receiver-operating-characteristic (ROC)-curve was performed for diagnostic ability of SPISE, HOMA-IR (homeostatic model assessment for insulin resistance), and HIRI (hepatic insulin resistance index), assuming null hypothesis of no difference in area-under-the-curve (AUC) at 0.5. RESULTS SPISE was lower in NAFLD (male: 4.8±1.2, female: 4.5±1.1) than in non-NAFLD group (male 6.0±1.6, female 5.6±1.5; P< 0.05 {95% confidence interval [CI]: male NAFLD 4.5, 5.2; male non-NAFLD 5.2, 6.8; female NAFLD 4.0, 5.1, female non-NAFLD 5.0, 6.2}). In males, ROC-AUC was 0.71 for SPISE (P=0.006, 95% CI: 0.54, 0.87), 0.68 for HOMA-IR (P=0.038, 95% CI: 0.48, 0.88), and 0.50 for HIRI (P=0.543, 95% CI: 0.27, 0.74). In females, ROC-AUC was 0.74 for SPISE (P=0.006), 0.59 for HOMA-IR (P=0.214), and 0.68 for HIRI (P=0.072). The optimal cutoff-level for SPISE between NAFLD and non-NAFLD patients was 5.18 overall (Youden-index: 0.35; sensitivity 0.68%, specificity 0.67%). CONCLUSION SPISE is significantly lower in juvenile patients with obesity-associated NAFLD. Our results suggest that SPISE indicates hepatic IR in pediatric NAFLD patients with sensitivity and specificity superior to established indices of hepatic IR.